New and emerging pharmacologic treatments for MDD - Uyar, Aslihan; Gonul, Ali Saffet (Frontiers in Psychiatry, 2025)
Major depressive disorder (MDD) presents a significant global health challenge, characterized by a high prevalence and significant impact on quality of life. Traditional antidepressants fall short in terms of efficacy and onset speed, up to 60% of patients. This review delves into the new and emerging pharmacologic treatments for MDD, focusing on their mechanisms of action, clinical effectiveness, and potential to fill the gaps left by conventional therapies. New and emerging treatments in MDD have centered on different neurobiological pathways than the traditional monoaminergic systems. Ketamine and its enantiomer, S-ketamine, have been highlighted for their rapid antidepressant effects, which act through non-competitive N-methyl-d-aspartate (NMDA) receptor antagonism and other pathways involving synaptic plasticity. Clinical trials have demonstrated the ability of ketamine to quickly reduce symptoms, particularly in treatment-resistant cases, with effects noticeable within hours and lasting several days post-administration. Furthermore, the combination of dextromethorphan and bupropion has shown promise. This formulation leverages the NMDA receptor antagonism and sigma-1 receptor agonism of dextromethorphan, complemented by the inhibition of monoamine uptake and metabolism by bupropion, resulting in quicker and more durable antidepressant effects compared with monotherapy. Neurosteroids such as brexanolone and zuranolone, which target γ-aminobutyric acid (GABA)-A receptors, have emerged as effective treatments for postpartum depression. Brexanolone, administered via infusion, and zuranolone, available as an oral formulation, both have demonstrated efficacy in clinical settings. Novel treatments targeting opioid pathways, such as esmethadone, and selective kappa receptor antagonists offer new hope for addressing the symptoms of MDD through mechanisms not traditionally associated with antidepressant action.